Effect of Age, Breed, and Sex on the Health-Related Quality of Life of Owner Assessed Healthy Dogs - Rodger, Susan; Scott, E Marian; Nolan, Andrea; Wright, Andrea K; Reid, Jacqueline (Frontiers in Veterinary Science, 2021)
Using an app, this study generated health-related quality of life (HRQL) information in a large cohort of dogs deemed healthy by their owner. It forms the basis for further studies investigating the natural history of HRQL of dogs to inform the interpretation of interventional studies, but highlights the risks of relying on owner impression of health status. A previously published HRQL instrument (VetMetrica™) that generates scores in four domains of quality of life in dogs - Energetic and Enthusiastic (E/E), Happy and Content (H/C), Active and Comfortable (A/C), Calm and Relaxed (C/R), generated information on HRQL in 4217 dogs (3months – 21years). Dogs were categorized by age; young, 3 – 47 months, middle-aged, 48 – 95 months, and old, 96 months and older. Owners considered 2959 dogs (3 – 95months) to be “in perfect health” and these were used to explore the relationship between age, sex, breed and HRQL in apparently healthy dogs. Mean score was significantly greater (better) in young compared to middle-aged dogs in E/E, H/C and A/C and declined with advancing age. In H/C there was a small but significant difference in mean score between female and male dogs (mean greater in females), with a similar rate of decline in each gender with advancing age. In E/E there were very small but statistically significant differences in mean scores between certain breeds. In A/C there was a statistically significant interaction between breed and age and the rate of decline with advancing age differed with breed. Overall, age, breed and sex predicted very little of the variation seen in HRQL scores. Data from a subset of 152 dogs, for whom clinical information was available, were used to examine the agreement between clinical evidence and owner opinion. According to the clinical records, 89 dogs were healthy and 63 had evidence of chronic disease. There was an approximately 40% disagreement between owner opinion on health status and clinical evidence of chronic disease (35% disagreement in all dogs and 43% in old dogs). HRQL scores were generally higher in dogs for whom there was no evidence of disease in the clinical record.